Histopathological and Immunohistochemical Characterization of Skin Biopsies From 41 SARS-CoV-2 (+) Patients: Experience in a Mexican Concentration Institute: A Case Series and Literature Review. (15th May 2022) - Quintero-Bustos, Gabriel; Aguilar-Leon, Diana; Saeb-Lima, Marcela
Abstract: The SARS-CoV-2 pandemic brought countless clinical and pathophysiological questions. Although mucocutaneous infections are the most visible, they are among the least studied. This article provides relevant information to characterize morphologically and immunohistochemically the dermatoses from patients with COVID-19, during the first year of the pandemic. Immunohistochemistry reactions against the spike protein were performed in 48 skin biopsies, and the positive cases were classified according to their histomorphology; at the end, 41 biopsies led us to identify 12 morphological patterns that mimic other skin pathologies, among which pityriasiform patterns predominate. For the literature review, we selected cases of SARS-CoV-2 dermatoses that included complete histopathological information and that were published during the same interval of time; after careful evaluation, 205 biopsies were selected and then classified into 8 groups according to previously published proposals. Dermatoses associated with SARS-CoV-2 are as diverse in their clinical expression as in their histopathology, mimicking entities totally unrelated to COVID-19. Furthermore, some of these groups are characteristically associated with an aggressive course of the disease. Undoubtedly, it is necessary to delve into the possibility that these findings are translatable into prognostic and therapeutic factors.